2016
DOI: 10.1016/j.jviscsurg.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Management of blunt hepatic trauma

Abstract: For the last 20 years, nonoperative management (NOM) of blunt hepatic trauma (BHT) has been the initial policy whenever this is possible (80% of cases), i.e., in all cases where the hemodynamic status does not demand emergency laparotomy. NOM relies upon the coexistence of three highly effective treatment modalities: radiology with contrast-enhanced computerized tomography (CT) and hepatic arterial embolization, intensive care surveillance, and finally delayed surgery (DS). DS is not a failure of NOM managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 33 publications
0
30
0
6
Order By: Relevance
“…NOM could be the choice depends on the severity of liver blunt trauma and associated injuries. 5,7 Kozar et al, in his study revealed that global complication rate of NOM is 14 % but for grade V injuries the rate was higher around 52%. 31 Grade of liver injury can reflect the degree of hepatic parenchymal damage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…NOM could be the choice depends on the severity of liver blunt trauma and associated injuries. 5,7 Kozar et al, in his study revealed that global complication rate of NOM is 14 % but for grade V injuries the rate was higher around 52%. 31 Grade of liver injury can reflect the degree of hepatic parenchymal damage.…”
Section: Discussionmentioning
confidence: 97%
“…Non-operative management of liver injuries has gained wide support and adopted for approximately 80% of blunt liver injuries. 7 This nonoperative approach was at first apply to pediatric patients and has been rapidly extended to adults. 2 It is contraindicated for hemodynamic instability and peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the numerous classification schemes in liver injury is of paramount importance in understanding the treatment options for these patients. There are four major classification systems which stratify various traumatic injuries by severity: the Abbreviated Injury Score (AIS), 10 the American Association for Surgery of Trauma (AAST) grading system, the Injury Severity Score, 11,12 and World Society of Emergency Surgery (WSES) grading system. 9 The AIS is an anatomically based global severity system that classifies injury severity by body region.…”
Section: Grades Of Liver Injurymentioning
confidence: 99%
“…NOM is achievable in an estimated 80% of all hepatic trauma cases. 11 To qualify for NOM, patients must be hemodynamically stable, have an adequate response to initial resuscitation attempts, and have no peritoneal signs. These patients should be imaged with multiphase CT immediately and treated according to imaging findings.…”
Section: Overview Of Management Of Hepatic Trauma In Adultsmentioning
confidence: 99%
See 1 more Smart Citation